2017
DOI: 10.1097/tp.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Discontinuation of Prednisone in Kidney Transplant Recipients

Abstract: Background Short- and intermediate-term results have been reported after rapid discontinuation of prednisone (RDP) in kidney transplant recipients. Yet there has been residual concern about late graft failure in the absence of maintenance prednisone. Methods From October 1, 1999, through June 1, 2015, we performed a total of 1553 adult 1st and 2nd kidney transplants—1021 with a living donor (LD), 532 with a deceased donor (DD)—under our RDP protocol. We analyzed the 15-year actuarial overall patient survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The BEST trial has implications for a number of transplant‐related complications. ESW experiences have shown reduced cardiovascular risk/cardiovascular events and improved cardiovascular survival; therefore, it seems reasonable that additional reduction in cardiovascular risk/events will be provided by simultaneous CNIA/ESW . Moreover, CNIA/ESW should further minimize drug‐related toxicity, specifically neurotoxicity, gastrointestinal toxicity, and NODAT, thereby enhancing quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BEST trial has implications for a number of transplant‐related complications. ESW experiences have shown reduced cardiovascular risk/cardiovascular events and improved cardiovascular survival; therefore, it seems reasonable that additional reduction in cardiovascular risk/events will be provided by simultaneous CNIA/ESW . Moreover, CNIA/ESW should further minimize drug‐related toxicity, specifically neurotoxicity, gastrointestinal toxicity, and NODAT, thereby enhancing quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors (CNIs) have been the cornerstone of immunosuppressive therapy in transplant for almost 4 decades. CNI‐based therapy, however, is complicated by significant adverse events, including hypertension, hyperlipidemia, and new‐onset diabetes after transplant (NODAT), leading to increased cardiovascular events and cardiovascular morbidity and mortality . CNIs are also associated with significant toxicities, including nephrotoxicity, neurotoxicity, and gastrointestinal (GI) toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prospective randomized studies comparing RDP with maintenance prednisone found no significant difference in patient survival, graft survival, or renal function at 5 years post‐transplant. In a single‐center analysis of 1st and 2nd transplant recipients, we found no difference in 15‐year patient or graft survival between those on RDP and those on maintenance prednisone . In a subanalysis of that study, we compared recipients with at least 5‐year graft survival on RDP ( n = 859) versus maintenance prednisone ( n = 317) and found no difference between groups in patient or graft survival between 5 and 15 years post‐transplant.…”
Section: Discussionmentioning
confidence: 88%
“…Patients exposed to higher corticosteroid doses or those who underwent corticosteroid treatment for longer durations were considered to be at a higher risk for AVN (2,22).…”
Section: Discussionmentioning
confidence: 99%